Google Sites Based on Guided Inquiry to Improve Social Studies Critical Thinking in Elementary Schools - Kori Sundari; Arita Marini; Nina Nurhasanah (Journal of Education Reseach and Evaluation, 2024)
The increase in Indonesian internet users will reach 215 million people in 2023, increasing from 77.02% to 78.18%. Apart from that, students' critical thinking, evaluation, inference, explanation and self-regulation skills still need to be improved. This research aims to develop Google sites based on guided inquiry. This type of research is development research using the Borg and Gall model procedure. The research subjects are learning media experts, material experts and language experts. The test subjects were 30 students and 2 teachers. Data collection methods use observation, interviews, questionnaires and tests. Data collection instruments use questionnaires and test questions. Data analysis techniques use descriptive statistical analysis and inferential statistical analysis. The results of the research were that media expert validation produced an average of 4.64, material experts produced an average of 4.67 and language expert validation results were 4.7. Based on teacher and student trials, it shows that the media is in the very good category, declared suitable for use in learning. The effectiveness test results obtained an N-gain of 56.2 in the "quite effective" category. Student response activities obtained an N-gain of 77.99 in the "effective" category. It was concluded that Google Sites-based media integrated with guided inquiry can improve the critical thinking of fifth-grade elementary school students compared to conventional learning. This research implies that the guided inquiry-based Google Sites developed can be used in learning.